Ditiola haasii (Basidiomycota, Dacrymycetaceae)—taxonomy and ecology of a rare species from Central Europe - Zamora, Juan Carlos; Holec, Jan (Phytotaxa, 2021)
Ditiola haasii, a largely unknown member of the Dacrymycetes described from Germany, is documented in detail based on two specimens collected on Picea abies wood in the Boubínský prales virgin forest, Czech Republic. The work represents the first complete taxonomic/ecological investigation of the species since its original description. The morphology of the newly studied samples is evaluated to gain a better knowledge of intraspecific variation, and a phylogenetic analysis based on nrLSU data is provided to further confirm our identification and show the phylogenetic position of D. haasii within the Dacrymycetes. A comparison with similar species and those with which it has been confused is made and ecological details are provided based on our collections. Colour photographs of basidiomata and micromorphological characters are published. Ditiola haasii is currently documented by just six records worldwide, all of them from Central Europe.